Greening the Paranormal: Exploring the Ecology of Extraordinary Experience edited by Jack Hunter - Rawlette, Sharon Hewitt (Journal of Scientific Exploration, 2020)
Far from a dispassionate survey of the intersection between ecology and parapsychology, Jack Hunter's anthology is a collection of the deeply personal insights and discipline-defying questions that have arisen from the contributors' lived contact with some of the strangest aspects of the natural world.